Perencanaan Moda Transprtasi Umum Rute Stasiun Tanjung Karang – Bandara Radin Inten II Lampung Selatan - Nazori, Azizi; Heriyanto, Dwi; Sulistiyorini, Rahayu (Universitas Lampung, 2015)
This study consisted of two phases, namely collecting primary datas required, such as passengercharacteristics, choice of transport modes, flight datas, the number of passengers on certainperiod of time, distance and travel time from the Tanjung Karang Station to Radin Inten II SouthLampung Airport. Then analyze it with some methods that are used as conclusion parameters.This study uses several parameters used as reference for the planned mode of transportationplanning, i.e. the percentage of the characteristics and mode choice questionnaire results,multinomial logistic, simple linear regression, and performance planning mode of transportationof the plan.From the analysis of the datas percentage of the number of passengers with journey from BandarLampung origin who have the willingness to switch to the planned mode of transportationamounted to 96.67% or 72.75% of total passenger aircraft. The approximate number ofpassengers who will use public transport development plan based on the number of passengers 5years ie in 2019 amounted to 3,057 people per day. Planned modes of transportation wereplanned start the movement from 05.00 am to 07.00 pm with a departure time between busvulnerable for 15 minutes. As for the trip Radin Inten II Airport South Lampung - Tanjung KarangStation planned start movement from 07.00 am to 09.00 pm with a departure time of 15 minutesvulnerable. Based on the results of the processing of survey data obtained estimates of the numberof passengers in 2019 as many as 27 passengers per trip. Therefore it is required the type oftransport that meet these criteria are buses with a capacity of 35 passengers or so-called mediumbus. Performance planning public transportation based on the results of the questionnaire surveydata processing and some suggestions of passenger aircraft with the results of the servicefrequency of 4 veh / hour, 15-minute headway time, load factor of 77.14%, cycle time of 150minutes, the vehicle needs a number 12 vehicles, vehicle mileage per day amounted to 282 km,traveling speed of not more than 100 km / hour, mileage per trip of 23.5 km.Keywords: Radin Inten II Airport Lampung Selatan, Tanjung Karang Station, transportationplanning, public transportation, Performance Planning Public Transportation.